2006
DOI: 10.1116/1.2402153
|View full text |Cite
|
Sign up to set email alerts
|

Low-stress silicon carbonitride for the machining of high-frequency nanomechanical resonators

Abstract: Articles you may be interested inStudy of the resonant frequencies of silicon microcantilevers coated with vanadium dioxide films during the insulator-to-metal transition J. Appl. Phys. 107, 053528 (2010); 10.1063/1.3309749 Silicon nanocluster-sensitized emission from erbium: The role of stress in the formation of silicon nanoclusters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…16,32 We have recently reported the development of a novel silicon carbonitride ͑SiCN͒ material of tunable mechanical properties for the fabrication of nanomechanical resonators. 15 The residual stress of this material can be controlled through postresidual anneal, allowing full access from compressive to tensile range. We here report the development of a fresh approach 7 to surface machining of suspended nanostructures that employs a combination of surface and bulk machining techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,32 We have recently reported the development of a novel silicon carbonitride ͑SiCN͒ material of tunable mechanical properties for the fabrication of nanomechanical resonators. 15 The residual stress of this material can be controlled through postresidual anneal, allowing full access from compressive to tensile range. We here report the development of a fresh approach 7 to surface machining of suspended nanostructures that employs a combination of surface and bulk machining techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoresonators and microresonators are traditionally fabricated by surface micromachining [14][15][16][17][18][19] that involves deposition of a sacrificial oxide layer followed by the structural layer, such as polysilicon, silicon nitride, silicon carbide, nanocrystalline diamond, or metal films. Suspended structures ͑cantilevers, bridges, etc.͒ are released by isotropic etch of the buried sacrificial layer.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting Cr metal pattern of a single resonator supported by two pads was used as a mask for the selective reactive ion etching of the SiCN layer using a 30 s 4:1 SF 6 :O 2 plasma recipe. 8 The Cr layer was etched away in a stock Cr etch solution composed of ceric ammonium nitrate, nitric acid, and water for 20 min. The doubly clamped resonators were finally released by an anisotropic wet etch in a 32% KOH solution saturated with isopropanol for etch durations ranging from 40 to 100 s.…”
Section: Methodsmentioning
confidence: 99%
“…7 Recently, Fischer et al reported the development and microstructural characterization of a novel silicon carbon nitride ͑SiCN͒ material for the fabrication of nanomechanical resonators. 8 The mechanical properties of SiCN can be tuned; e.g., the thin film stress of SiCN can be controlled through a postdeposition anneal, allowing full access from compressive to tensile range. Fischer et al further reported the development of a resonator nanomachining approach combining surface and bulk micromachining techniques with small undercuts and the potential for nanoscale resonators with a high yield.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental methods for making thin films of SiCN to facilitate sensor fabrication are being researched worldwide. Radio frequency magnetron sputtering [4,5], pulsed laser deposition [6], plasma-enhanced chemical vapor deposition (CVD) [7], microwave plasma-enhanced CVD and electron cyclotron resonance plasma CVD [8], ion beam sputtering [9], hotwire CVD [10] and other methods of depositing SiCN films have been explored. The advantages of catalytic CVD over PECVD and other deposition techniques include higher deposition rate with lower strain, reduced thermally induced stress on the substrate and low processing cost.…”
mentioning
confidence: 99%